Ti(Oi-Pr)4-Promoted Regio- and Stereoselective Aminolysis of 2,3-Epoxy Amides - Righi, Giuliana; Mantineo, Agnese; Suber, Lorenza; Mari, Alessandra (Synlett, 2012)
A mild and inexpensive Ti(Oi-Pr)4-mediated aminolysis of 2,3-epoxy amides has been developed. The reaction proceeds with excellent regioselectivity, regardless of the steric hindrance of the substituents on the heterocyclic ring, providing vicinal amino alcohols that are very suitable for synthetic applications.
Keywords: amides; diastereoselectivity; epoxides; regioselectivity; ring opening